Soft Magnets from the Self‐Organization of Magnetic Nanoparticles in Twisted Liquid Crystals1. (2nd September 2014) - Matt, Benjamin; Pondman, Kirsten M.; Asshoff, Sarah J.; ten Haken, Bennie; Fleury, Benoit; Katsonis, Nathalie
Abstract: Organizing magnetic nanoparticles into long‐range and dynamic assemblies would not only provide new insights into physical phenomena but also open opportunities for a wide spectrum of applications. In particular, a major challenge consists of the development of nanoparticle‐based materials for which the remnant magnetization and coercive field can be controlled at room temperature. Our approach consists of promoting the self‐organization of magnetic nanoparticles in liquid crystals (LCs). Using liquid crystals as organizing templates allows us to envision the design of tunable self‐assemblies of magnetic nanoparticles, because liquid crystals are known to reorganize under a variety of external stimuli. Herein, we show that twisted liquid crystals can be used as efficient anisotropic templates for superparamagnetic nanoparticles and demonstrate the formation of hybrid soft magnets at room temperature.